Pengujian Usability untuk Mengetahui Kepuasan Pengguna pada Website Perpustakaan Institut Teknologi Telkom Purwokerto - Jahfal Rizqi Putra Pradhana; Metha Khafifah Isty Rikhanah; Renna Nur Injiyani; Wildan Hanif Ardiansah; Zanuar Rahmat Saputra; Faisal Dharma Adhinata; Diovianto Putra Rakhmadani (Journal ICTEE, 2021)
The coronavirus pandemic makes human activities, in particular work, change. At first, when working face-to-face for discussions or other supporting activities, now everyone requires using an online virtual system that can be accessed from anywhere to prevent the spread of the coronavirus. Website-based information systems are no stranger to society because most have accessed information through certain websites. Institut Teknologi Telkom Purwokerto created a web-based application to support book lending activities or libraries' activities. This website requires testing to determine the level of user satisfaction in accessing the website, whether it is according to user expectations or not. One of the testing techniques to assess the feasibility of a website from user responses is usability testing. We created a questionnaire to look at several aspects of the test: learnability, flexibility, effectiveness, and attitude. The test results from 12 respondents showed that the ITTP library website usability test reached 79.45%, which means that this website is suitable for use.